Integration social media technology and ethical collaborative learning - Ataie, Fariba (2018)
The research aimed to design and evaluate an innovative Web 2.0-based collaborative learning (CL) with the Islamic ethical system to support the problematic issues of CL and enhance its opportunities in the application domain. This study planned practicing Web 2.0-based CL based on the social constructivist theory for formal and informal learning under the guidelines of Design Science Research Methodology (DSRM) in order to enhance learners' motivation, engagement, critical thinking, self-regulation, skills in the use of knowledge in real life, endurance, self-control, empathy and religious awareness that are highlighted in International Islamic University Malaysia (IIUM) goals. This is in response to the lesser amount of focus on integrating information communication technology (ICT) into the CL that could promote learning goals. There is an urgent need to create intervention programmes to increase ICT self-efficacy and ability to use social media for CL. The most important argument in the learning process is that the students should be given a practical platform where they can practice collaboratively and share their experiences that DSRM and Facebook features in this study could support these needs and arguments. The principle of design was planned based on seven guidelines of DSRM that emphasis on using IT artifact considering available opportunities to solve wicked problems and using rigorous methods in both the construction and evaluation process. A three-phase well-executed evaluation was considered for measuring utility, effectiveness, quality, and ethicality of developed artifact and assessing how it is used to improve the problematic situation and enhance opportunities. In the un-instantiation phase of evaluation, the theoretically developed artifact was reviewed and validated by experts. Secondly experienced students among informal learners participated in the pilot study, evaluated and compared developed artifact potential for CL with LMS. In the third phase instantiation evaluation and user testing were conducted with three cycles of design-evaluation; 42 students in two courses, used Facebook secret group in developed artifact for formal and academic learning and shared own experiences with application domain through public page and groups. A Questionnaire, participant observation, interviews and focus group were used for evaluating artifact and CL process. Findings showed the positive perception of students about the artifact and its effectiveness in promoting CL goals. The triangulation among different source of data showed developed artifact potential for self-regulation, practice ethical CL in the virtual world and use in real life that promotes the goals of the study circle program and centre for Islamisation. The CL and social negotiation with empathy, research, and teamwork using artifact contributed to the goals of IIUM World Debate and Oratory Center that emphasise on research and critical thinking. Additionally, with the aim of generalising the research results and improving the validity and quality of the artifact, this study communicated with application domain varying the situation in terms of types of people and setting. The findings from measuring Iranian Telegram users' perception about artifact showed the perceived usefulness and self-efficacy have a significant influence on users' intention to use the artifact. The comprehensive model for developing web 2.0- based CL that is this study's framework, IT artifact evaluation model that is research design and developed Web 2.0 based CL are contributions of this study to the knowledge base. Thus, this study could be as a real example of integrating ICT into CL with DSRM in Information System.